Pengaruh Strategi Pemasaran Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Coffee Shop Coffhouse Di Cengkareng - Eva Fitriani Aritonang; Rani Rani; Purwatiningsih Purwatiningsih (Institut Nalanda, 2023)
This study aims to analyze the influence of marketing strategies and service quality on coffee shop Coffhouse customer satisfaction. The research method used is quantitative research using primary data through the distribution of questionnaires to Coffhouse customers. The study sample consisted of 75 respondents. The collected data were analyzed using the SPSS 25 program using multiple linear regression analysis techniques. The results showed that: 1) there was a positive and significant influence between marketing strategies on customer satisfaction which was shown from the calculated results of 11,653 with a significant 0,000. 2) There is a positive and significant influence between service quality and customer satisfaction as shown from the results of a calculation of 4,111 with a significant 0,000. 3) there is a positive and significant influence between marketing strategy and service quality on customer satisfaction, this is shown by the Fcalculate value of 380,319 with a significant value of 0,000. With a large influence of 91.1% while the remaining 8.9% was influenced by other variables outside the study